Adaptive Smoothing Technique for Remotely Sensed Images Enhancement - Muhsin, J. J. (Iraqi Journal of Physics, 2008)
Spatial and frequency domain techniques have been adopted in this search. meanvalue filter, median filter, gaussian filter. And adaptive technique consists ofduplicated two filters (median and gaussian) to enhance the noisy image. Differentblock size of the filter as well as the sholding value have been tried to perform theenhancement process.